2018
DOI: 10.1055/a-0614-2871
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary co-infection with nocardia species and nontuberculous mycobacteria mimicking miliary tuberculosis in a patient with Crohn’s disease under combined immunosuppressive therapy

Abstract: Nocardiosis is a rare infection caused by ubiquitous soil-born, acid-resistant, Gram-positive bacteria that can be life-threatening in immunocompromised patients. Originally usually diagnosed in HIV-positive patients, only few cases have been reported in patients on immunosuppressive therapy for inflammatory bowel disease or rheumatologic disorders. We present a case of a 32-year-old man who was treated with infliximab, prednisolone, and azathioprine for severe terminal ileitis. Although the clinical status im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Compound sulfamethoxazole was effective for nocardiosis in glomerular disease patients and even for disseminated nocardiosis, which was characterized by diminished subcutaneous and pulmonary abscesses as a therapeutic response. It has been suggested that nocardiosis mainly occurs in patients suffering from autoimmune diseases, chronic Abbreviation: WBC White blood cell, N% Percentage of neutrophils, CRP C reactive protein, PCT Procalcitonin, ALB Serum albumin, Sr Serum creatinine, 24 h UP 24-h urinary protein *: P < 0.05, compared to data before treatment; a : All the data in "after treatment" were obtained when antibiotic treatment stopped renal disease, hematological diseases and HIV infection, especially in those who receive glucocorticoids or other immunosuppressive treatments [29,[35][36][37][38]. Here, we observed that all 7 patients with nocardiosis had been receiving glucocorticoids alone or combined with immunosuppressive agents, which is consistent with the previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…Compound sulfamethoxazole was effective for nocardiosis in glomerular disease patients and even for disseminated nocardiosis, which was characterized by diminished subcutaneous and pulmonary abscesses as a therapeutic response. It has been suggested that nocardiosis mainly occurs in patients suffering from autoimmune diseases, chronic Abbreviation: WBC White blood cell, N% Percentage of neutrophils, CRP C reactive protein, PCT Procalcitonin, ALB Serum albumin, Sr Serum creatinine, 24 h UP 24-h urinary protein *: P < 0.05, compared to data before treatment; a : All the data in "after treatment" were obtained when antibiotic treatment stopped renal disease, hematological diseases and HIV infection, especially in those who receive glucocorticoids or other immunosuppressive treatments [29,[35][36][37][38]. Here, we observed that all 7 patients with nocardiosis had been receiving glucocorticoids alone or combined with immunosuppressive agents, which is consistent with the previous literature.…”
Section: Discussionmentioning
confidence: 99%